Basic Statistics Using Excel to accompany Statistical Techniques in Business and Economics - A. Lind Douglas (MC Graw Hill, 2008)
By Merchant, Goffinet, and Koehler is a workbook that introduces students to Excel and shows how to apply it to introductory statistics. This manual presumes no prior familiarity with Excel or statistics and provides step-by-step directions in a how-to style using Excel XP and text examples and problems.